TLR4/MD2 specific peptides stalled in vivo LPS-induced immune exacerbation. (May 2017) - Park, Seolhee; Shin, Hyeon-Jun; Shah, Masaud; Cho, Hey-Young; Anwar, Muhammad Ayaz; Achek, Asma; Kwon, Hyuk-Kwon; Lee, Byugsung; Yoo, Tae Hyeon; Choi, Sangdun
Abstract: Negative regulation of Toll-like receptor-4 (TLR4) is anticipated to control the pathogen-induced exaggerated immune response. However, effective TLR4 antagonists with scarce off-target effects are yet to be developed. To fill this void, we sought to design small peptide-inhibitors of the TLR4/MD2−LPS interaction. Here we report novel TLR4-antagonistic peptides (TAP), identified through phage display, endowed with the LPS-induced proinflammation inhibition, and confirmed in mice. TAPs-attributed TLR4-antagonism were initially evaluated through NF-κB inhibition in HEK-blue hTLR4 and RAW264.7 cells, and further reinforced by the downregulation of MAPKs (mitogen-activated protein kinases), NF-κB, interleukin 6, and suppression of the oxidative-stress products and iNOS in macrophages and human peripheral blood mononuclear cells (hPBMCs). Among these, TAP2 specifically halted the TLR4, but not other TLRs signaling, which was further confirmed by the biophysical kinetic assay. Finally, TAP2 diminished LPS-elicited systemic cytokine response in vivo, suggesting that TAPs, specifically TAP2, have the potential to treat TLR4-mediated immune ailments.